2022
DOI: 10.1063/5.0077397
|View full text |Cite
|
Sign up to set email alerts
|

Generalized approach to plasmonic phase modulation in topological bi-gratings

Abstract: We study the role of optical momenta in surface plasmon excitation by topological bi-gratings. We analyze plasmonic structures composed of rectangular apertures rotating in 2D space with given rates, which couple to specific plasmon trajectories. We experimentally demonstrate the control of plasmonic propagation through premeditated design of the gratings, which interact with linear, spin, and orbital angular momentum of light. We show that these trajectories can be selected purely through momenta modulation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The momentum deviation of the satellites from each ordinary diffraction order corresponds to k s = 2π/ N Λ. This resembles the results achieved in topological plasmonic gratings comprised of local anisotropic apertures rotated from θ = 0 to θ = π in N steps . In the current experiment, the satellites are attributed to the geometric phase appearing due to the spatially varying chirality.…”
Section: Resultssupporting
confidence: 83%
“…The momentum deviation of the satellites from each ordinary diffraction order corresponds to k s = 2π/ N Λ. This resembles the results achieved in topological plasmonic gratings comprised of local anisotropic apertures rotated from θ = 0 to θ = π in N steps . In the current experiment, the satellites are attributed to the geometric phase appearing due to the spatially varying chirality.…”
Section: Resultssupporting
confidence: 83%
“…Previous work 22 has shown that the total momentum of a topological diffraction mode from a periodic grating with spatial rotation of the unit-cell can be described via the following equation: where is the incident momentum of the beam (with being the wavelength and is the incidence angle) and is the fundamental momentum quanta imparted by the grating with a period of . Here we suppose that both, the actual grating periodicity and the rotation of the unit-cell are along the same axis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work 22 has shown that the total momentum of a topological diffraction mode from a periodic grating with spatial rotation of the unit-cell can be described via the following equation:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A grating comprising spatially rotating apertures was used to obtain two effects simultaneouslycoupling incident light to SPs and imparting upon that light a geometric phase. As a result, the illumination of the structure by right-handed (or left-handed) circular polarization (RCP, LCP respectively) led to the unidirectional spin dependent excitation of the SP modes 22 . There the fundamental grating periodicity and its rotation rate were constant along the structure giving rise to a periodic diffraction pattern as could be expected from the Bloch-Floquet theorem.…”
Section: Introductionmentioning
confidence: 99%